Diversity and Variation of Asymbiotic Nitrogen-Fixing Microorganisms in Alpine Grasslands on the Tibetan Plateau - Li, Wenyan; Li, Fei; Zeng, Haijun; Ma, Lin; Qi, Lingyan; Wang, Xiaochun; Wang, Wenyin; Peng, Zhen; Degen, A. Allan; Bai, Yanfu; Zhang, Tao; Huang, Mei; et al. (Frontiers in Ecology and Evolution, 2021)
Asymbiotic nitrogen-fixing (ANF) bacteria contribute a substantial amount of nitrogen in ecosystems, especially in those with low symbiotic nitrogen fixation capability. Degradation of alpine grassland is widespread on the Tibetan Plateau and sown grassland has become one of the main strategies for grassland restoration. However, the diversity and community structure of ANF bacteria in different grassland types remain unknown. The aim of this study was to fill this gap. Soil samples were obtained from 39 grassland plots selected from three counties in the eastern Tibetan Plateau. The plots were classified as natural grassland (NG), sown grassland (SG), lightly degraded grassland (LDG) and severely degraded grassland (SDG). Asymbiotic nitrogen-fixing microbial communities of the four grassland types were compared at the level of community and species diversity by 16S rRNA high-throughput sequencing technology. The phylum Proteobacteria accounted for > 72% of the ANF bacteria. The community structures of soil ANF bacteria differed significantly (p< 0.01) among grassland types. We concluded that: 1) planting gramineous forage could possibly mitigate the decrease in diversity of soil ANF bacteria caused by grassland degradation; and 2) the diversity of soil ANF bacteria in alpine grassland of the Tibetan Plateau is closely related to grassland degradation and restoration.